2019
DOI: 10.1007/978-981-13-6101-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Water Scarcity for Economic Growth

Abstract: Organisation de Coopération et de Développement Économiques Organisation for Economic Co-operation and Development 08-Aug-2016 ___________________________________________________________________________________________ _____________ English -Or. English ENVIRONMENT DIRECTORATE IMPLICATIONS OF WATER SCARCITY FOR ECONOMIC GROWTH -ENVIRONMENT WORKING PAPER No. 109 by Thomas W. Hertel (1), Jing Liu (1)(1) Purdue University, USA OECD Working Papers should not be reported as representing the official views of the OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Where changes are marginal or happen at a small scale, these feedback can be ignored (as is the case study explored in this paper, since the economic relevance of the RMBM in the wider basin and regional scale is limited). However, where changes are not marginal, large‐scale structural changes in the crop portfolio can lead to impacts on prices through feedback into the output of economic sectors at a regional and supraregional scale (Hertel & Liu, ). As the economy transitions toward a new equilibrium, commodity prices, including those relevant for agriculture, will change, thus affecting irrigators' decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Where changes are marginal or happen at a small scale, these feedback can be ignored (as is the case study explored in this paper, since the economic relevance of the RMBM in the wider basin and regional scale is limited). However, where changes are not marginal, large‐scale structural changes in the crop portfolio can lead to impacts on prices through feedback into the output of economic sectors at a regional and supraregional scale (Hertel & Liu, ). As the economy transitions toward a new equilibrium, commodity prices, including those relevant for agriculture, will change, thus affecting irrigators' decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results indicated that countries like Sudan, Ethiopia, and Ethiopia, and Kenya have a higher WF. Water is intertwined with a variety of economic activities, and it has many diverse channels by which it influences human and economic development [102]. The advancement of the socioeconomic and environmental processes cannot work without the help of a long-term WEFBH scheme [103].…”
Section: Dynamics Of Vwc and Wf Of Cropsmentioning
confidence: 99%
“…Freshwater supply has been altered worldwide due to human-induced changes, like habitat degradation, anthropogenic subsidence, climate-related risks, and the increasing disproportionate water consumption [1][2][3]; causing water scarcity and salinization in some regions and flooding in others [4][5][6]. Besides, the agricultural activity prompts natural water overexploitation and pollution [7].…”
Section: Introductionmentioning
confidence: 99%